The influence of anthropomorphism on children's learning and attitudes toward snakes - Reider, Lori Beth; LoBue, Vanessa (Frontiers in Developmental Psychology, 2024)
Previous research suggests that negative information contributes to the development of fear. The current study examined whether using anthropomorphic input can alter children’s attitudes toward snakes, a commonly feared animal. Children from the United States (N = 89; Mage = 5.43 years; 47 females, 42 males) heard a story about a snake that did (n = 44) or did not (n = 45) contain anthropomorphic information, and we examined the effect of anthropomorphic input on children’s attitudes, learning, and willingness to help snakes. After hearing either story, children reported less fear of snakes. Further, while children in the anthropomorphic condition were more likely to attribute anthropomorphic qualities to snakes, there were no differences in the amount of information children learned. Most importantly, children in the anthropomorphic condition prioritized helping snakes more than children in the neutral condition. These findings demonstrate the impact of anthropomorphic information on children’s attitudes and learning.